Keefektifan Kombinasi Media Filter Zeolit Dan Karbon Aktif dalam Menurunkan Kadar Besi (Fe) dan Mangan (Mn) pada Air Sumur - Purwonugroho, Nasrudin, Dwi Astuti, SKM., M.Kes, Sri Darnoto, SKM., MPH (2013)
The degree of Fe and Mn substances in water which are higher than quality standard can create technical, physical, and health disruption. The degree of Fe and Mn substances in Griya Fajar Regency in Gentan, Baki, Sukoharjo is higher than the standards accepted (2.910 mg/l and 0.900 mg/l). The decrease of the degree of Fe and Mn can be conducted by filtration using combination of zeolite filter and active carbon media. The purpose of this research was to find the effectiveness of the combination of zeolite filter and active carbon media in decreasing the degree of Fe and Mn. The research used experiment method applying the research design of pretest and posttest with control group. The population in this research was all wells in Griya Fajar Regency 09/XII. Total sample used in the research was 60 liters. Each treatment needs 5 liters with three times repetition. The statistics test used one-way anova. The result of the statistics test shows that there was effectiveness of the combination of zeolite filter and active carbon media in decreasing the degree of Fe and Mn. The measurement result of the average degree in control of Fe and Mn was 2.897 mg/l and 0.877 mg/l. the treatment used zeolite filter media show the average degree of fe and Mn was 0.160 mg/l and 0.137 mg/l, while the treatment used active carbon media show the average degree of Fe and Mn was 0.217 mg/l and 0.247 mg/l. using both media, the average degree of Fe and Mn was 0.183 mg/l and 0.247 mg/l. the most effective combination in decreasing the degree of Fe and Mn was Zeolite with effectiveness of 94.50% and